Pascu-Rønning Type Meromorphic Functions Based on Sălăgean-Erdély–Kober Operator - Sheza M. El-Deeb; Gangadharan Murugusundaramoorthy; Kaliappan Vijaya; Alhanouf Alburaikan (Axioms, 2023)
In the present investigation, we introduce a new class of meromorphic functions defined in the punctured unit disk <semantics><mstyle scriptlevel="0" displaystyle="true">Δ*:={ϑ∈C:0<|ϑ|<1}</mstyle></semantics> by making use of the Erdély–Kober operator <semantics><msubsup>Iς,ϱτ,κ</msubsup></semantics> which unifies well-known classes of the meromorphic uniformly convex function with positive coefficients. Coefficient inequalities, growth and distortion inequalities, in addition to closure properties are acquired. We also set up a few outcomes concerning convolution and the partial sums of meromorphic functions in this new class. We additionally state some new subclasses and its characteristic houses through specializing the parameters that are new and no longer studied in association with the Erdély–Kober operator thus far.